Urban Forest Management: A Primer to Strategic Planning for Municipal Governments - Michael Andreu; Robert Northrop; Wayne Zipperer (EDIS)
This publication is an introduction to Urban Forest Management: A Primer to Strategic Planning for Municipal Governments, available in full for free here: https://ffgs.ifas.ufl.edu/urbanforestmanagementbook/.